Renewal of Criminal Law Politics Relating to Justice Based On Justice - Adhi Budi Susilo (Walisongo Law Review (Walrev), 2019)
Copyright is a high reality of various values, including economic value, this is because copyright that is born of copyright, taste, and intention is able to color the development of human life through objects born from the copyright process. However, in its development various copyrights were not considered in this country. The rise of piracy on song copyrights for example, is only able to benefit the perpetrators of piracy of song copyright economically. The research method used is a juridical legal research method of analysis with the object of research studies aimed at the laws and regulations relating to copyright and principles - applicable legal principles. Substantially, the material changes in Law No. 28 of 2014 is related to the change of type of criminal offense from ordinary offense to complaint offense and in the meantime there are not many creators who can seek justice about it. The results of the research are increasingly unfair with the existence of Clause 112 to Clause 119 of Law Number 28 of 2014 changing copyright offenses to complaint offenses that increasingly marginalize the rights of the creators of copyrighted works in this country. Therefore it is necessary to have a joint discussion related to the political development of criminal law related to copyright offenses. Hak Cipta adalah suatu realitas yang tinggi akan berbagai nilai, termasuk didalamnya nilai ekonomis, hal ini dikarenakan hak cipta yang lahir dari cipta, rasa, dan karsa mampu mewarnai perkembangan kehidupan umat manusia melalui benda yang lahir dari proses cipta tersebut. Namun dalam perkembangannya berbagai hak cipta tidaklah diperhatikan di negara ini. Maraknya pembajakan akan hak cipta lagu misalnya, hanya mampu menguntungkan bagi oknum pelaku pembajakan hak cipta lagu tersebut secara ekonomis,  Metode penelitian yang digunakan adalah metode penelitian hukum yuridis analisis dengan objek kajian penelitian yang ditujukan terhadap peraturan perundang-undangan yang berkaitan dengan hak cipta dan prinsip-prinsip hukum yang berlaku. Secara substansial, materi perubahan dalam UU No. 28 Tahun 2014 adalah yang berkaitan dengan perubahan jenis tindak pidana dari delik biasa menjadi delik aduan serta sementara itu pihak pencipta tidak banyak yang dapat mengupayakan keadilan akan hal itu. Hasil dari penelitian semakin bertambah tidak adil dengan adanya Pasal 112 hingga Pasal 119 Undang-Undang Nomer 28 Tahun 2014 merubah delik hak cipta menjadi delik aduan yang semakin memarjinalkan hak dari pencipta suatu karya cipta di negara ini. Oleh sebab itu perlu adanya pembahasan bersama terkait pembangunan politik hukum pidana terkai delik hak cipta.